1845-64 Or. Gen. Laws 530-31, ch. 43, § 524-25 - (:unkn) unknown (My University, 1864)
If any person shall challenge another to fight a duel, or transmit the message for another shall be guilty of a misdemeanor
Keywords: DUELING